SHRINKING PROJECTION METHOD WITH ALLOWABLE RANGES - Takeuchi, Y. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
In this note, we introduce an iterative method with allowable ranges which is a revised version of the shrinking projection method. Allowable ranges associated with the method are related to errors caused by a corresponding numerical calculation method.